Exploring Innovative Teaching Methods and Technologies in Ugandan Classrooms - Afam Uzorka; Ademola Olatide Olaniyan (Journal of Research in Education and Pedagogy, 2025)
Due to the pressing need to improve educational quality and accessibility, Uganda’s educational system is significantly transitioning. Adopting cutting-edge teaching strategies and technologies has become crucial as the nation works to fulfil the demands of a world that is changing quickly. This study explores innovative teaching methods and technologies in Uganda classrooms using a qualitative research design to understand how these innovations are being implemented and what opportunities and difficulties they bring. 54 people from 10 Ugandan universities participated in the study. Purposive sampling was used in the participant selection process to guarantee a varied representation of experiences and points of view. Through semi-structured interviews, data was gathered. The data from the interviews were analyzed using thematic analysis. Four major themes emerged: Culturally Relevant Pedagogy, Personalized Learning, Active Learning Strategies, and Technology Integration in Education. The results show that although technology improves student engagement and instructional delivery, issues such as resource scarcity and inadequate teacher preparation prevent it from reaching its full potential. Active learning techniques encourage teamwork and critical thinking, but they run into problems with big class sizes and a lack of resources. While there is potential for personalized learning to meet a wide range of learner demands, it will cost a lot in terms of professional development and adaptive technology. To create inclusive learning settings, culturally specific pedagogy is necessary, but it must be matched with standardized curricula. To optimize the advantages of these cutting-edge methods in Ugandan education, this study emphasizes the necessity for better infrastructure, teacher support, and equitable resource allocation.